Application of Velocity Variation with Angle (VVA) Method on an Anisotropic Model with Thomsen Delta Anisotropy Parameters - Waskito Pranowo; Sonny Winardhi (Jurnal Geofisika, 2018)
Anisotropic properties will influence seismic propagation, for example it will affect wave velocity. One of well-known anisotropi equation for Transversaly Isotropic media is weak anisotropy with Thomsen's notation. Supriyono [2011] tried to estimate all of these variables by using velocity variation with angle (VVA) attribute. This research uses synthetic data, which is CMP Gather to know limitations of VVA attribute, to identify the error values, and to determine the best indicator of anisotropic eect. This research also uses another analysis method, which is grid search inversion to estimate VP0. From this research, Both VVA and grid search invesion still produce signcant error. The effects which will appear because of anisotropic property's presence are hockey-stick and over NMO-stretching.